Conselho Municipal de Educação de Uberlândia-MG: possibilidades na democratização da educação municipal (2009-2012) - Silva, Maria Adelina Cantalogo (2013)
This investigative paper aimed to m ake an analysis of the political participation in the Educational Municipal Board, during 2009 to 2012 and its possibilities about democratization of the municipal educational management. To achieve such goal, a case study was made about the Uberlândia‟s Educational Municipal Board , MG. The used methodologies were: content and documental analysis. The data collection was made based on primary documents gathered on the Uberlândia‟s Educational Municipal Board official file and verifying actions, during august 2011 and September 2012. The documentation used were: municipal laws that composes its legal structure, ordinary meeting chronograms; guidelines and proceeding of ordinary and extraordinary meetings; developed activities report, official organogram and organ‟s judgment. In this case, we initially bring the origin and conceptions about the boards structure, further considering the Education‟s board trajectory in Brazil, evaluating them about the Union, considering States and Municipals, whose genesis bring historical marks of advisement to the governs, of each historical moment. Subsequently, we made a brief bibliographical survey introducing some theoretical indications about: 1 democracy, focusing particularly to the modern representative democracy, about its difficulties on obtaining the wishing values of political equality and popular sovereignty, in a complex capitalist society, 2 democratic management, emphasizing the power issues and the deficiency of its implementation; 3 participation, describing its shapes, kinds, degree and levels and the contextualization of political participation. Going through, we present the UEMB political participation analysis, pointing contradictions and attempting to answer the aim of this paper.